Vertical asymmetry absence on covert orientation of visual attention (Research, Society and Development, 2021)
Attention is as a set of processes leading to the selection or prioritization of information, filtering the latter and avoiding perceptual overload in the processing of stimuli. Several brain functions are lateralized such as speech and spatial processing. The orientation of attention is more processed in the right hemisphere, favoring the right visual space. The present study aimed to investigate vertical asymmetries of attention. For this purpose, an adaptation of the Posner's Attention Paradigm (1980) with central clues was used. Thirty-six subjects participated in the experiment, healthy men and women. The results showed no vertical asymmetry in the covert orientation of visual attention, both for reaction times and for the percentage of errors. There is a possible asymmetry in the longer SOA, with a slight favoring of the superior visual field. Future work should investigate whether symmetry in the orientation of visuospatial attention is supported by equivalent neural activation, differently from what happens for the orientation of attention in the horizontal plane.